Aortic Dissection Presenting as Acute Pancreatitis: Suspecting the Unexpected - Adam Hafeez; Dillon Karmo; Adrian Mercado-Alamo; Alexandra Halalau (Case Reports in Cardiology, 2018)
Aortic dissection is a life-threatening condition in which the inner layer of the aorta tears. Blood surges through the tear, causing the inner and middle layers of the aorta to separate (dissect). It is considered a medical emergency. We report a case of a healthy 56-year-old male who presented to the emergency room with sudden onset of epigastric pain radiating to his back. His blood pressure was 167/91 mmHg, equal in both arms. His lipase was elevated at 1258 U/L, and he was clinically diagnosed with acute pancreatitis (AP). He denied any alcohol consumption, had no evidence for gallstones, and had normal triglyceride level. Two days later, he endorsed new suprapubic tenderness radiating to his scrotum, along with worsening epigastric pain. A MRCP demonstrated evidence of an aortic dissection (AD). CT angiography demonstrated a Stanford type B AD extending into the proximal common iliac arteries. His aortic dissection was managed medically with rapid blood pressure control. The patient had excellent recovery and was discharged home without any surgical intervention.